COVID-19 in Africa: can the recent pandemic spur investments in healthcare infrastructure development? - Senyo Dotsey (Springer, 2024)
Abstract The COVID-19 pandemic has had varying impacts on different populations around the world. In some developing regions, particularly Africa, the pandemic has not resulted in high mortality rates but has exposed significant deficiencies in healthcare infrastructure. This analysis underscores the urgent need for governments to prioritize substantial investment in healthcare infrastructure development, aiming to strengthen the capacity of African nations to effectively tackle global health crises. The commentary provides specific, actionable recommendations that can empower African governments to better prepare for and respond to future health emergencies.